PENGEMBANGAN POTENSI KEPEMIMPINAN KADER ORGANISASI KEMAHASISWAAN: PENGEMBANGAN POTENSI KEPEMIMPINAN KADER ORGANISASI KEMAHASISWAAN - Roy Setiawan; Dedy Triyono (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
ABSTRACT Leadership potential must be developed in an effective and efficient way to improve self-quality and organizational performance. This service activity is carried out with the aim of exploring the leadership potential of cadres or prospective leaders of Student Organizations in Higher Education as national cadres, so it is hoped that these cadres can lead Student Organizations well as a miniature of a pluralistic society as. This leadership potential development activity is essential to carry out with the hope of becoming a positive contribution to cadres to equip them to carry out their duties as leaders of Student Organizations.